Differences in the Prevalence of Fruit and Vegetable Consumption in Spanish Workers - Ronda-Pérez, Elena (Nutrients, 2020)
The present study aims to examine the differences in daily fruit and vegetable consumption in the working population in Spain. A cross-sectional study was conducted, using data from the 2017 National Health Survey (n = 10,700 workers aged between 18 and 65 years). The daily consumption of fruit and vegetables was evaluated using two items included in a food frequency questionnaire. Occupations were classified into the 17 main groups of the National Classification of Occupations of 2011 (CNO-11). The prevalence (P) of daily fruit and vegetable consumption was calculated in relation to sociodemographic characteristics, health behaviors, work-related characteristics and occupations. Logistic regression analysis was performed to examine the association, with simple and adjusted Odds Ratio (aOR). The P of daily consumption of fruit and vegetables in workers was 60% for fruit and 40% for vegetables. After adjusting for sociodemographic characteristics and health behaviors, workers working night or rotating shifts had a lower consumption of fruits (aOR:0.9; p < 0.05), and those working on temporary contracts had a lower consumption of vegetables (aOR:0.8; p < 0.05). Engineers, scientists, health care workers and teachers had the highest fruit consumption (74.5%) and the highest vegetable consumption (55.1%). The lowest consumption of fruits was presented by the military (42.3%) and unskilled workers in the service sector (45.8%), and the lowest consumption of vegetables was presented by skilled construction workers (25.5%). These findings could aid in workplace health promotion and could be used in future studies to evaluate the impact of the activities adopted.